The safety of bendamustine in patients with chronic lymphocytic leukemia or non-Hodgkin lymphoma and concomitant renal impairment: a retrospective electronic medical record database analysis. Issue 6 (June 2014) - Nordstrom, Beth L.; Knopf, Kevin B.; Teltsch, Dana Y.; Engle, Robert; Beygi, Hooman; Sterchele, James A.
Abstract This retrospective study compared adverse-event rates in patients with chronic lymphocytic leukemia (CLL) or non-Hodgkin lymphoma (NHL), with and without renal impairment, receiving bendamustine alone or with rituximab. Patients (n = 940) were stratified into a renally impaired group (creatinine clearance [CrCL] < 40 mL/min) and two comparator groups (CrCL ≥ 40 mL/min and CrCL ≥ 60 mL/min). Renally impaired patients with NHL had a significantly greater incidence of grade 3–4 thrombocytopenia compared with the CrCL ≥ 60 mL/min group (hazard ratio [HR], 2.57; p = 0.025). For CLL and NHL together, grade 3–4 increased blood urea nitrogen was significantly higher in the renally impaired group than in the CrCL ≥ 40 mL/min (HR, 2.36; p = 0.02) and CrCL ≥ 60 mL/min (HR, 4.46; p = 0.001) groups. Based on these results, monitoring blood counts (including platelets) and renal function would be prudent in the management of patients with renal dysfunction and NHL or CLL who receive bendamustine-based regimens.